Ready-To-Assemble (RTA) Furniture: Bedroom Laptop Table - Ng, Jen Nee; Ab Hamid, Abdullah Al Rashid (Research in Management of Technology and Business, 2023)
A laptop table is a type of furniture that can be put anywhere and will provide convenience to users when they are working. Ready-to assemble furniture would provide a great opportunity for people to construct their own furniture with the use of screws, hinges, and other readily available supplies. Most office employees and students are forced to stay at home to complete online activities due to the COVID-19 pandemic. The purpose of this research is to create a laptop table that satisfies people's needs. Long periods of time spent with a laptop on your legs might cause skin damage. The scope of this study was limited to the bedroom. The target users are university students from Universiti Tun Hussein Onn Malaysia. Research, design development, and mock-up are the three key areas of research. Solid wood, wood composites, plastic, ceramic, marble, and other materials can beused to produce furniture. A questionnaire is used to investigate each item of furniture in order to establish the design of the laptoptable, including its kind, form, material, colour, and more. Thumbnails and ideation, idea development, and mock-ups are all elements in the design creation process. The survey collected data on people's perceptions of laptop table designs from 50 respondents. This study will serve as guidelines and additional value in the future, primarily to fulfill people's demands and desires for design.